O que determina a variação do crânio em mamíferos? Avaliando as regras de Rensch e de Bergmann em primatas da América do Sul - Polidoro, George Lucas Sá (2016)
In this study our aim was to analyze if Rensch and Bergmann rules apply to South-American primates of the genera Sapajus and Alouatta, where males tend to be larger than females and if species tend to be larger at higher latitudes. We found that Alouatta and Sapajus show similar Rensch's rule trend, and found a reverse Bergmann pattern for Alouatta (size larger at smaller latitudes), a pattern which is dependent of both phylogenetic and spatial autocorrelations. Both sexes of both genera, size is explained by vegetation complexity and enviroment, thus size variation is not only explained by taxonomy but also by adaptations related to the environment pressures.